Mechanical properties of dense to porous alumina/lanthanum hexaaluminate composite ceramics - Negahdari, Zahra; Willert-Porada, Monika; Pfeiffer, Carolin (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2010)
For development of new composite materials based on lanthanum hexaaluminate and alumina ceramics, a better understanding of the microstructure-properties relationship is essential. In this paper, attention was focused on the evaluation of mechanical properties of lanthanum hexaaluminate/alumina particulate composite. It was found out that the lanthanum hexaaluminate content plays a critical role in determination of the microstructure and mechanical properties of the composite ceramics. In situ formation of plate-like lanthanum hexaaluminate in the ceramic matrix was accompanied with formation of pores so that the microstructure shifted from dense to porous. Increasing the lanthanum hexaaluminate content up to a certain value enhanced the fracture toughness, increased the hardness, and increased the elastic modulus of the composite materials. Further increase in the lanthanum hexaaluminate content degraded the hardness as well as the elastic modulus of composite ceramics. The influence of lanthanum hexaaluminate on mechanical properties was described by means of microstructure, porosity, and intrinsic characteristics of lanthanum hexaaluminate. © 2010 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Ceramics; Composites; Hardness measurement; Mechanical characterization; Nanoindentation; Porous materials